Effects of Increasing Chloride Concentrations on Growth Performance of 15- to 25-lb Nursery Pigs - D. Shawk; K. N. Nemechek; R. D. Goodband; J. C. Woodworth; M. D. Tokach; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 300 nursery pigs (initially 15.5 lb; Line 241 × 600; DNA, Columbus, NE) were used in a 21-d trial to determine effects of increasing dietary Cl on nursery pig growth performance. Upon entry to the nursery, pigs were allotted by BW and fed a common starter diet (0.33% Na and 0.76% Cl) for 7 d. On d 7 after weaning, considered d 0 in the trial, pens were assigned to 1 of 6 dietary treatments that were fed from d 0 to 14. Experimental treatments included a control diet containing 0.33% Na and 0.55% Cl provided by 0.78% added salt, or 5 diets with 0.33% Na and added potassium chloride to provide 0.09, 0.21, 0.32, 0.45, or 0.55% Cl. A common diet (0.18% Na and 0.49% Cl) was then fed from d 14 to 21. From d 0 to 14, ADG, ADFI, and F/G improved (quadratic, P<0.05) as dietary Cl increased from 0.09 to 0.32% with no further benefits observed thereafter. Pigs fed the 0.55% Cl diet had greater (P<0.05) ADFI, but tended (P = 0.053) to have poorer F/G than pigs fed the control diet with 0.55% Cl from added salt. Pigs fed the control diet and the 0.55% Cl diet had similar ADG. When pigs were fed the common diet from d 14 to 21, ADG decreased (linear, P = 0.045) and ADFI increased (linear, P = 0.033) in pigs previously fed increasing dietary Cl concentration. Pigs previously fed increasing Cl concentration had poorer (quadratic, P<0.001) F/G. Pigs previously fed the 0.55% Cl diet had greater (P = 0.009) ADFI but tended (P = 0.059) to have poorer F/G than pigs previously fed the control diet with 0.55% Cl from added salt. There was no evidence of difference to indicate that previously feeding the control diet or the 0.55% Cl diet affected ADG. From d 0 to 21, ADG improved (quadratic, P = 0.002) as dietary Cl increased from 0.09 to 0.32% with no further benefits observed thereafter. Average daily feed intake increased (linear, P = 0.002) as dietary Cl increased. Pigs fed the 0.55% Cl diet had increased (P<0.05) ADFI but poorer F/G than pigs fed the control diet with no evidence of difference to indicate that dietary treatments affected ADG. In conclusion, results of this study indicate a dietary Cl concentration of 0.32% would optimize ADG, ADFI, and F/G of 15 to 25 lb pigs, which is slightly lower than the NRC current estimate of 0.45%.
Keywords: chloride; nursery pig; salt; sodium